Municipal solid waste generation, composition and management: issues and challenges. a case study - Ahsan, Amimul; Aziz, Mohammad Gulzarul; Kamal, Md. Rowshon; Idrus, Syazwani; Alamgir, M.; Imteaz, Monzur; Shams, Shahriar (Technical University of Wroclaw, 2015)
Khulna is the third largest metropolitan city in Bangladesh and a centre with intensive commercial and industrial activities. Rapid urbanization and increased migration of people from rural and coastal areas has put tremendous pressure on its existing solid waste management. The status of the existing municipal solid waste (MSW) management tiers such as generation, source storage, collection, on-site storage, transportation, and open dumping has been identified in this study. The daily generation of MSW is estimated as 520 Mg, of which food and vegetable wastes are the main components (79% on average). The major source of generated MSW is residential areas, which is 85.87% of total generation, whereas 11.60% in commercial areas, 1.02% in institutional areas, 0.55% in street sweeps and 0.96% in other areas. About 50% of total generated waste is disposed daily to the dumping site and the rest remains uncollected and unmanaged. Non-governmental organizations and community based organizations play an important role in primary collection, composting of organic wastes and medical waste management.